Failure of dabigatran and rivaroxaban to prevent thromboembolism in antiphospholipid syndrome: a case series of three patients - Schaefer, Jordan K.; McBane, Robert D.; Black, David F.; Williams, Lindsy N.; Moder, Kevin G.; Wysokinski, Waldemar E. (Thrombosis and Haemostasis, 2014)
Direct oral factor inhibitors (DOFIs) are an attractive alternative to vitamin K antagonists (VKA) for the treatment of patients with antiphospholipid syndrome (APS). In the absence of prospective, randomised trial data, reports of therapeutic failures in clinical practice alert clinicians to potential limitations of DOFI therapy for this indication. Data for all cases were collected from a centralised system that contains complete medical records of all patients treated and followed at Mayo Medical Center. We present here three consecutive APS patients who had had no thromboembolism recurrence on warfarin but were switched to DOFIs. The diagnosis of APS was established according to currently recommended criteria. The three cases were as follows: A woman with primary APS developed thrombotic endocarditis with symptomatic cerebral emboli after transition to dabigatran. A second woman with primary APS experienced ischemic arterial strokes and right transverse-sigmoid sinus thrombosis after conversion to rivaroxaban. A man with secondary APS suffered porto-mesenteric venous thrombosis after switching to rivaroxaban. None of these patients had failed warfarin prior to the transition to DOFIs. Based on these three cases, we advocate caution in using DOFIs for APS patients outside of a clinical trial setting, until further data becomes available.
Keywords: Direct oral anticoagulants; warfarin; antiphospholipid syndrome; thromboembolic complications